Qualidade fisiológica de sementes, crescimento e partição de assimilados em plantas de rabanete submetidas a diferentes concentrações de metais - Moraes, Rita de Cássia Pinheiro de (2012)
Toxic metals are compound that settle naturally from the rocks and they are release slowly in the soil by mineral weathering. The essential elements for plant nutrition when in higher concentrations can produce harmful effects to vegetable. The radish is a short cycle vegetable, it was used because can be employed in rotation with other economic cultures, and also it has been characterized for several searchers that aim as a model species to study heavy metals such as: Zn, Pb and Cd. For that reason, the work was done in order to evaluate the seeds physiologic quality, characteristics of growth, and assimilate partition in radish plants grown under different concentrations of metals. The research was realized in three experiments, the first was conducted in the Seeds Physiological Laboratory of DB/UFPel, measuring the physiologic quality of the radish seeds cv. Vip Crimson S Special treated with different concentrations of CuSO4 (0, 35 and 70 mgL-1), Al2 (SO4 )3 (0, 10, 20 and 30 mgL-1) and MnCl2 (0, 270 and 540 mgL-1), through tests of viability and vigor. The second and third assays were conducted in greenhouse of DB/UFPel with objective to determine the growth characteristics and assimilate partition, during the ontogeny of the plants grown under three concentrations of each metal: Al2 (SO4)3 (0, 20 and 40 mgL-1) and MnCl2 (0, 540 and 810 mgL-1). Also was determined the metals contain at the final harvest. The experimental design was entirely randomized in a factorial scheme (1 x 3 x 8), where one cultivar, three concentrations and eight harvest. The primary data were adjusted by logistic simple or polynomial regression. In general, the application of metal increased the percentage of germination as well as the rate of seeds germination. In addition, all characteristics of growth were augmented by metals. However, the manganese induced higher growth than the aluminum but both were always superior to plants control. The parameters evaluated on third assay following the same tendency and the metals did not showed phytotoxicity. The Mn accumulated preferentially on shoots while Al priority on roots of radish. Then, the radish was tolerant for both metals on concentrations tested, being plant with potential to remedy soil with harmful acidity caused by Al and Mn.